KIAT KOMUNITAS TANAH OMBAK MENGEMBANGKAN SENI BUDAYABAGI ANAK-ANAK DENGAN LATAR SOSIAL NELAYAN DI PURUS KOTA PADANG - Ella Miftah Aulia; Indrayuda (Universitas Negeri Padang, 2025)
This study aims to uncover the strategies employed by the Tanah Ombak Community in developing arts and culture for fishermen's children in Purus, Padang City. Using a descriptive qualitative approach, data were collected through observation, interviews, literature review, and documentation. This study describes the interactions between the community and its members, the surrounding community, and the wider community. The results show that the Tanah Ombak Community has a specific strategy: unconditionally accepting fishermen's children, fostering them through arts activities such as storytelling, poetry reading, and theater, guided directly by community administrators and volunteers. In addition, the community also holds non-arts activities such as learning to recite the Quran, reading, mobile libraries, and mutual cooperation. These activities have received a positive response from the community, resulting in parents encouraging their children to actively participate in community activities. This community has received various awards from the Ministry of Education and Culture and has been covered by national media such as Mata Najwa, CNN Indonesia, MNC TV, and Net TV. With an inclusive and educational approach, this community has succeeded in fostering interests and talents in arts and literacy among fishermen's children, while strengthening their character and cultural identity. This research is expected to serve as a reference in developing arts and culture-based community management for marginalized environments.